Estimating glacier-bed overdeepenings as possible sites of future lakes in the de-glaciating Mont Blanc massif (Western European Alps) - Magnin, Florence; Haeberli, W.; Linsbauer, A.; Deline, P.; Ravanel, Ludovic (Geomorphology, 2020)
International audience De-glaciating high mountain areas result in new landscapes of bedrock and debris where permafrost can degrade, persist or even newly form in cases, and of new lakes in glacier bed overdeepenings (GBOs) becoming ice-free. These landscapes with new lakes in close neighborhood to over-steepened and perennially frozen slopes are prone to chain reaction processes (e.g. rock-ice avalanches into lakes triggering impact waves, dam breach or overtopping, and debris flows) with potentially far-reaching